Pembentukan Karakter Religius Siswa Melalui Program Pembiasaan Ibadah Di SMA Ma’arif NU Sokaraja - Febriana Rani; Moh. Hanif (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
In the Millennial Era or Gen Z, moral decline and a crisis of religious character are major challenges in the world of education. This research is motivated by the importance of strengthening religious identity in students in a school environment based on Islamic values. From a sociological perspective, education is not only a location for transferring knowledge, but also a primary place for socialization where religious norms are internalized through interaction and social order. This researcher aims to explore how students' religious character is formed through the implementation of the worship habit program at SMA Ma'arif Nu Sokaraja, and to identify the elements that contribute to its success. The method used in this study is a qualitative approach with descriptive methods. Data collection was carried out using participatory observation techniques on religious activities in the school, interviews with the principal, Islamic religious education teachers, general subject teachers, and students, and also involved documentation studies. The data analysis process was carried out in three steps: data reduction, data presentation, and drawing conclusions to obtain a comprehensive picture of the process of internalization of religious values. The main results of this study indicate that the formation of religious character at SMA Ma'arif NU Sokaraja is carried out in a planned manner through certain habits: repeatedly (such as reading Asmaul Husana, congregational Dhuhur prayer, student cults, istighosah, the culture of asking and shaking hands, as well as role models from educators.